2018
DOI: 10.24215/16666038.18.e21
|View full text |Cite
|
Sign up to set email alerts
|

Short term cloud nowcasting for a solar power plant based on irradiance historical data

Abstract: This work considers the problem of forecasting the normal solar irradiance with high spatial and temporal resolution (5 minutes). The forecasting is based on a dataset registered during one year from the high resolution radiometric network at a operational solar power plan at Almeria, Spain. In particular, we show a technique for forecasting the irradiance in the next few minutes from the irradiance values obtained on the previous hour.  Our proposal employs a type of recurrent neural network known as LSTM, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Additionally, in this kind of time series, it is recommended to limit the dataset according to some specific hours in which the variables to be predicted take a significant value. As an example, for solar radiation, it is common to restrict data to diurnal hours [26,30]. In this case, only nocturnal hours were considered, from 23 p.m. to 7 a.m. the next day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in this kind of time series, it is recommended to limit the dataset according to some specific hours in which the variables to be predicted take a significant value. As an example, for solar radiation, it is common to restrict data to diurnal hours [26,30]. In this case, only nocturnal hours were considered, from 23 p.m. to 7 a.m. the next day.…”
Section: Methodsmentioning
confidence: 99%
“…Other research presented a short-term cloud forecast based on irradiance historical data collected in a radiometric network in Almeria (Spain) [30]. When applying a recurrent neural network known as Long Short-Term Memory (LSTM), they concluded that this method shows improvement in comparison with other common methods used for time series analysis.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…In addition, due to its ability of removing abundant information to resolve vanishing gradient issues, LSTM is appropriate to represent the learning data over different temporal domains [17]. Hence, LSTM has been studied in solar forecasting during the past five years [15,17,44,[53][54][55][56][57][58][59][60][61][62][63]. For instance, the first study regarding LSTM [64] demonstrated its forecasting skills for one-day ahead utilizing remote-sensing data under various topographical conditions with the best root mean square error (RMSE)~24% and mean absolute error (MAE)~17%.…”
Section: Introductionmentioning
confidence: 99%